Expression network analysis reveals cord blood vitamin D-associated genes affecting risk of early life wheeze. Issue 2 (18th July 2018) - Mirzakhani, Hooman; Al-Garawi, Amal A; Carey, Vincent J; Qiu, Weiliang; Litonjua, Augusto A; Weiss, Scott T
Abstract : Cord blood 25-hydroxyvitamin D (25OHD) has been reported in association with risk of early life recurrent wheeze. In a subset of infants who participated in the Vitamin D Antenatal Asthma Reduction Trial, we demonstrated that higher cord blood 25OHD at birth (>31 ng/mL) was associated with a reduced risk of recurrent wheeze in the first year of life. We then identified a module of co-expressed genes associated with cord blood 25OHD levels >31 ng/mL. Genes in this module are involved in biological and immune pathways related to development and progression of asthma pathogenesis including the Notch1 and transforming growth factor-beta signalling pathways.